1991
DOI: 10.1093/oxfordjournals.humrep.a137292
|View full text |Cite
|
Sign up to set email alerts
|

Return of reproductive performance after expectant management and local treatment for ectopic pregnancy

Abstract: The purpose of this study was to examine hysterosalpingographic findings and reproductive performance in patients previously managed non-surgically for ectopic pregnancy. Forty-nine patients with unruptured ectopic pregnancies were treated either by expectant management (n = 16) or medically (n = 33), using transvaginal methotrexate or sulprostone injection. The treatment was successful in 35 patients (71.5%), 12 out of 16 and 23 out of 33 in the two groups respectively. For all patients, follow-up currently v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…When appropriate inclusion criteria are used (Fernandez et al, 1991a), methotrexate failure rates have been similar to those reported in previous series of laparoscopic surgery (Pouly et al, 1986;Seifer, 1997). Moreover, follow-up and reproductive outcomes have been similar in both treatments (Pouly et al, 1986;Fernandez et al, 1991bPansky et al, 1993;Stovall and Ling et al, 1993). The simplicity and the results of this non-surgical approach demanded further investigation.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…When appropriate inclusion criteria are used (Fernandez et al, 1991a), methotrexate failure rates have been similar to those reported in previous series of laparoscopic surgery (Pouly et al, 1986;Seifer, 1997). Moreover, follow-up and reproductive outcomes have been similar in both treatments (Pouly et al, 1986;Fernandez et al, 1991bPansky et al, 1993;Stovall and Ling et al, 1993). The simplicity and the results of this non-surgical approach demanded further investigation.…”
Section: Introductionsupporting
confidence: 57%
“…When an ectopic pregnancy was visualized by transabdominal or transvaginal ultrasound, the patient was evaluated to determine her suitability for medical treatment (Fernandez et al, 1991b). This pretherapeutic score is based on six criteria graded on a scale from 1 to 3: gestational age, HCG and progesterone concentration, abdominal pain, haemoperitoneal volume, and diameter of the haematosalpinx, both the latter assessed by ultrasound.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of intrauterine pregnancies of 83.7% was similar to the findings of previously published studies, which reported intrauterine pregnancies in 65–89% of women following expectant management of tubal ectopics4–7. The cumulative 3‐year intrauterine pregnancy rate after salpingectomy was 46%, which was comparable to the rate of 38% published by Mol et al in 19982.…”
Section: Discussionsupporting
confidence: 88%
“…Expectant management is not often used in clinical practice and all studies published so far included a relatively small number of patients4–9 (Table 1). The aim of our study was to assess reproductive outcomes following expectant management of ectopic pregnancy in a large number of patients treated in a single center.…”
Section: Introductionmentioning
confidence: 99%
“…Without that evidence, practice can only be based on small observational studies. There is observational evidence to suggest that the avoidance of surgery may be associated with a decreased recurrent ectopic pregnancy rate, and slightly improved future intrauterine pregnancy rates31–36. Needless to say, conservative management is free from operative laparoscopy and anesthetic risks.…”
Section: Discussionmentioning
confidence: 99%